THU0656 IMMUNE CHECKPOINT INHIBITORS IN PATIENTS WITH CANCER AND RHEUMATOLOGIC DISEASES: A SYSTEMATIC REVIEW OF THE LITERATURE. (June 2019) - Abdel-Wahab, Noha; Safa, Houssein; Lopez-Olivo, Maria A.; Diab, Adi; Suarez-Almazor, Maria
Abstract : Background: Immune checkpoint inhibitors (ICI) have resulted in unprecedented advances in the treatment of cancer, with remarkable survival benefits, unseen with traditional treatment. While the benefits of ICI have been clearly documented, a myriad of immune-related-adverse events (irAEs) have been recognized in multiple organs and systems, secondary to persistent activation of the immune system. Objectives: To systematically review the literature and provide an updated summary on adverse events associated with the use of ICI therapy in patients with cancer and rheumatologic diseases. Methods: Five electronic databases were searched through 2018 with no restrictions. Articles were screened and selected by two independent investigators using a 2-step approach. Case reports, series, and observational studies describing patients diagnosed with rheumatologic disease prior to initiation of ICI for treatment of concomitant cancer were included. Results: A total of 69 patients in 27 publications were identified. Median age was 65 (38-87) years; 50% were female; 90% had metastatic melanoma; and 64% were receiving anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4) antibody. Rheumatoid arthritis was the most common in 64% (n=32). Other rheumatologic diseases included 16 spondyloarthropathy (7 psoriatic arthritis, 4 ankylosing spondylitis, 1 reactive arthritis, and 4 unspecified), 8 sarcoidosis, 6 vasculitis (3 eosinophilic granulomatosis with polyangiitis, and 1 each with granulomatosis with polyangiitis, Behcet's diseases, and polymyalgia rheumatica), 2 each with systemic lupus erythematosus and scleroderma, and 1 each with rheumatic fever, Sjögren's syndrome, and myositis. Overall, 73% (n=50) had an adverse event after initiation of ICI; 33% (n=32) had an exacerbation of the underlying disease, and 55% (n=38) had de novo irAEs. Patients with active diseases at ICI initiation seemed to have more disease flare than those with inactive disease (61% vs. 29%; p = 0.03), while no differences were observed in de novo irAEs (36% vs. 39%). Patients with rheumatoid arthritis were reported to have more flares with anti-CTLA-4 antibody (63% vs. 33%), while those with spondyloarthropathy reported more flares with anti-programmed cell death 1 agents (63% vs. 29%); however numbers were small. Patients receiving immunosuppressive therapy at ICI initiation had fewer adverse events than those not receiving treatment (26% vs. 44%). Most flares and irAEs were managed with corticosteroids, and 13% required additional disease modifying anti-rheumatic drugs. Adverse events improved in 64% and did not require discontinuation of ICI therapy. In melanoma patients, disease control rate was 44%. In all patients, no treatment related mortality was reported. Conclusion: About one third of patients with pre-existing rheumatologic autoimmune disease flared after receiving ICI therapy for treatment of cancer. However, flares and irAEs can often be managed and may not require discontinuation of cancer therapy. Prospective longitudinal studies are needed to evaluate potential differences among diseases and to determine optimal toxicity therapy while conserving antitumor immunity. Disclosure of Interests: : None declared